Sistema alternativo metodológico de las planificaciones de las capacidades físicas en las clases de educación física en los niños del sexto año de básica de la unidad educativa Lauro Damerval ayora N: 1 de la ciudad de Loja, 2015. - Gonzalez Camaño, Magali Banesa (2016)
The research work is aimed to know: methodological alternative system schedules the physical abilities in the classes of physical culture in children 6 th year of primary, the problematic situation detected in your object is given by the lack of a methodological system schedules the physical abilities in physical education classes, these factors have a significant impact on the development of methodological alternative system of students at the time of developing the physical abilities in physical education classes. It is aimed at improving the physical capabilities through a methodological alternative system of students of the Education Unit N1 Lauro Damerval Ayora. The categories of study: Physical Education, Physical and planning capabilities. The methodology used direct observation survey and test as technical and inductive deductive methods to perform the literature review, empirical, scientific and statistical information to achieve the desired. The results demonstrate the lack of a methodological alternative system planning physical abilities in the classes of physical culture in students and implement the proposal is satisfactory. In discussing empirical strategies used by the teacher they are revealed. In conclusion, the teacher does not use appropriate during physical education classes methodological strategies. It is recommended elaborates a training plan to optimize the pedagogical faculty of Physical Education of the Education Unit N1 Lauro Damerval Ayora, the city of Loja processes. The proposal aims to use an alternative system methodologic physical abilities in physical education classes to achieve quality education.